PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X SOSIAL 2 MA DARUL HIKMAH PEKANBARU - Ivo Rahmadini Lubis; Zulkarnain Zulkarnain; Rini Dian Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to improve learning process and increase student’s mathematical achievement through implementation of Problem Based Learning (PBL) Model. This type of research is Classroom Action Research with two cycle. The research was conducted in class X Social 2 MA Darul Hikmah Pekanbaru in the second semester of the 2017/2018 academic year. The subject of this research consist of 14 boys. The research instrument consists of learning materials and instruments for collecting data. Learning materials used in this research are the Syllabus, Lesson Plan and Activity Sheets. Instrument data collectors used in this research are observation sheet and mathematical achievement test. Data analysis techniques in this study are descriptive narrative analysis of qualitative data and descriptive statistics analysis of quantitative data. The result of this research showed that the implementation of PBL improved the student’s mathematical achievement. The percentage of students which is pass Minimum Mastery Crieria (MMC) increase from 14,28% to 35,17% at the first test and to 57,14% at the second test. This research concludes that the implementation of PBL improved the learning process and the student’s mathematical achievement at class X Social 2 MA Darul Hikmah Pekanbaru. PBL model can be used as an alternative to learning, because through this learning can improve the learning process and mathematical achievement of the students.Key Words: Classroom Action Research, Problem Based Learning models, Learning outcomes,Learning Process,